PENERBITAN JURNAL ILMIAH VISI PTK-PNF TAHUN 2006-2011 - Mita Septiani (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2012)
Scientific journal is a publication or promotion of scientific investigation in certain field. Journal of VISI PTK-PNF is published to meet the nEed of information on human resources in the nonformal education in Indonesia. The journal has been managed under a joined cooperation between Directorate of PTK-PNF, Ministry of National Education and The School of Education, State University of Jakarta since 2006. This article present and analyses the topics published to give a view of information in each edition. The information in this article is expected to be useful for researchers or potential writers in developing their topics to be published in this journal.